A contemporary review of enzymatic applications in the remediation of emerging estrogenic compounds. Issue 15 (3rd August 2022) - Zdarta, Jakub; Nguyen, Luong N.; Jankowska, Katarzyna; Jesionowski, Teofil; Nghiem, Long D.
Abstract: The occurrence of emerging contaminants, such as estrogens, in secondary and tertiary treated effluents and in sewage-impacted water bodies is one of the major obstacles to the implementation of water reuse. This review critically evaluates the performance of emerging process of enzymatic degradation of estrogens, and its efficiency. The data collected from peer-review literature show that enzymes have been extensively applied (in both free and immobilized form) in estrogen removal. Amongst others, the use of laccase as a catalyst provides over 90% removal of estrogens. Immobilized enzymes can overcome some limitations of the free biocatalysts, including reusability. Research evidence points to the formation of by-products, such as dimers and trimers. Nevertheless, estrogenic activity assessment indicates a reduction in toxicity after enzyme treatment. The cost and stability of enzymes, as well as their performance in a real wastewater matrix, are the major obstacles to the implementation of enzymatic processes in wastewater treatment. Continued endeavors are required to enhance the successful application of enzymes in the wastewater treatment industry. Highlights: Processes of enzyme-supported conversion of estrogens are reviewed and discussed. Laccase is the most commonly applied enzyme and achieves over 90% estrogen removal. Immobilization is suggested as an effective tool for enhancement of estrogen removal. Dimers and trimers have been identified as main bioconversion products of estrogens. Existing research gaps are highlighted and future recommendations are provided. Graphical abstract: